Azerbaijan – Kazakhstan relations: current situation and prospects - Huseynov, Rusif (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
Azerbaijan and Kazakhstan should not be seen as two states which are close because of their Soviet past. In fact, the titular ethnic groups of Azerbaijan and Kazakhstan – Azerbaijanis and Kazakhs – come from a greater Turkic family. Azerbaijani-Kazakh brotherhood takes its roots from the very origins of the Turkic peoples that spread from the Altai Mountains and has been cemented by the Islamic factor. Maintaining maritime borders through the Caspian Sea, Azerbaijan and Kazakhstan are important nations for one another. Azerbaijan is seen as a bridge for Kazakhstan to access Turkey and Europe, while Kazakhstan offers Azerbaijan routes to Central Asia and China. The two countries attach great importance to their mutual relations, both bilateral and within various international organizations. These relations have only increased and not experienced any downturns or problems in the past 25 years. Kazakhstan recognized the territorial integrity of Azerbaijan, which is an important deal for Azerbaijan in its current conflict with neighboring Armenia. The countries even reached an agreement on the legal status of the Caspian Sea quite rapidly, while similar accords are still absent with other littoral countries. They are both interested in developing an East-West transport and energy corridor, enjoying a favorable geopolitical location that could serve as a bridge between the continents.

Azerbejdżanu i Kazachstanu nie należy postrzegać jako dwóch państw, które są bliskie sobie tylko ze względu na radziecką przeszłość. W rzeczywistości zamiszkujące Azerbejdżan i Kazachstan grupy etniczne – Azerowie i Kazachowie – pochodzą z większej rodziny narodów tureckich. Braterstwo azero-kazachskie datuje się od samych początków narodów tureckich, które rozprzestrzeniły się z Gór Ałtaju i zostało ugruntowane przez czynnik islamski. Mające wspólną granicę morską na Morzu Kaspijskim Azerbejdżan i Kazachstan są dla siebie ważnymi narodami. Azerbejdżan jest postrzegany jako pomost dający Kazachstanowi dostęp do Turcji i Europy, zaś Kazachstan oferuje Azerbejdżanowi połączenie z Azją Centralną i Chinami. Oba państwa przywiązują wielką wagę do swoich wzajemnych relacji, zarówno dwustronnych, jak i w ramach organizacji międzynarodowych. Relacje te stale się rozwijają i w przeciągu ostatnich dwudziestu pięciu lat trend ten nie zmienia się, ani nie napotyka żadnych przeszkód. Kazachstan uznał terytorialną integralność Azerbejdżanu, co stanowi dla Azerbejdżanu ważne osiągnięcie wobec obecnego konfliktu z sąsiednią Armenią. Oba kraje szybko osiągnęły nawet porozumienie w sprawie statusu prawnego Morza Kaspijskiego, podczas gdy w innych krajach nadmorskich podobnych porozumień nie udało się wypracować. Oba państwa są zainteresowane rozwojem korytarza transportu i energetyki Wschód–Zachód, pozwalającego wykorzystać ich korzystną lokalizację geopolityczną, dzięki której mogą służyć jako pomost między kontynentami.
Stosunki Azerbejdżan–Kazachstan: obecna sytuacja i perspektywy
Keywords: Azerbaijan; Azerbejdżan; Kazakhstan; Kazachstan; Aliyev; Alijew; Nazarbayev; Nazarbajew; Nagorno-Karabakh; Górny Karabach; Turkic; tureckie; Caspian; kaspijskie; oil; ropa; Silk Road